Monitoring the Hydrological Activities of Antarctic Subglacial Lakes Using CryoSat-2 and ICESat-2 Altimetry Data - Yi Fan; Weifeng Hao; Baojun Zhang; Chao Ma; Shengjun Gao; Xiao Shen; Fei Li (Remote Sensing, 2022)
Monitoring the hydrological activities of subglacial lakes is critical to understanding the subglacial hydrological system and evaluating the internal mass changes of the Antarctic ice sheet. Drainage or filling events of active lakes lead to elevation changes in the ice surface. These changes can be observed by satellite altimetry, but the monitoring must be conducted continuously since the water movements in active subglacial lakes may occur frequently. We used CryoSat-2 Baseline-D and ICESat-2 data from 2010 to 2020 to obtain the time series of the ice surface elevation changes for 17 active lakes. We also evaluated the uncertainty of the time series derived from the CryoSat-2 data by cross-validation. The mean and RMS of the biases between the CryoSat-2-based and ICESat-2-based time series are generally less than 0.3 m and 1.0 m, respectively. However, the mean and RMS are greater over the lakes with rough ice surfaces, such as Whillans6, KT1, Mac3, and Slessor23. The drainage and filling events continue exhibiting in the extended period and the hydrological activities of SLW, L12, Whillans6, L78, and Mac1 occurred periodically. Furthermore, we inferred the hydrological connections between the lakes combining simulated water pathways.